Chlorpyrifos impaired cerebellar oxidative and cholinesterase activities in rats: Mitigating efficacy of Nigella sativa Oil - Imam, Aminu; Salaudeen, Barakat Oyindamola; Oyewole, Aboyeji Lukuman; Muhammad, Asma'u Shehu; Oyegbola, Christianah; Jaji-Sulaimon, Rukayat; Sulaimon, Fatimo Ajoke; Afodun, Adam Moyosore; Ajao, Moyosore Salihu (Nepal Journal of Neuroscience, 2021)
Background: Motor dysfunctions are some of the characteristic symptoms of organophosphate (OP) poisoning and they have been associated with decreased levels of cholinesterase inhibition within motor areas of the brain.Objectives: The current study aims to investigate the potential neuroprotective effects of Nigella sativa oil (NSO) in alleviating chlorpyrifos (CPF) induced toxicity in the cerebella and motor cortices of the rat brains using combined behavioural, biochemical and histochemical methods.Methods: Thirty-two rats were randomly divided into four groups (eight rats per group), exposed to 1ml/kg of normal saline, 14.9 mg/kg of CPF, 14.9 mg/kg of CPF plus 1ml/kg of NSO and 1ml/kg of NSO respectively for 14 consecutive days. The rats were each exposed to a single trial of the Open Field Test (OFT) on day 13 of the experiment. This experimental test measured locomotor activity levels (line crossing frequency (LCF)) and exploratory (rearing frequency (RF)) activities in the rats studied. The rats were euthanized on day 15 of the experiment and the brains were subsequently excised. The cerebella cortices of five brains were removed and homogenised to analyse for total reactive oxygen species (ROS), nitric oxide (NO) levels and acetylcholinesterase (AChE) activity. The motor and cerebella cortices from three other brains in each group were processed for histology (Nissl stain) and proliferative activity (Ki67 immunohistochemistry).Results: Rats exposed to CPF experienced a significant increase in cerebella NO and ROS levels, depletion in AChE activity, neurogenic cells loss and subsequent reduction in locomotor and exploratory behaviours respectively (LCF and RF). However, interventional treatment with NSO depleted markers of oxidative damage (NO and ROS), reduced AChE inhibition, preserved neurogenic (Ki67) cells distribution and motor functions.Conclusion: These results demonstrate the potential efficacy of NSO in OP poisoning and the roles of neurogenic and oxidative functions in the pathophysiology and treatment of motor dysfunction in OP neurotoxicity.